Safe Storage of Gametes and Embryos: No Time for Complacency - Tomlinson, Mathew James (Seminars in Reproductive Medicine, 2018)
Recent serious untoward incidents in the field of assisted reproduction have once again highlighted the need for vigilance and in particular improved risk management in relation to the cryopreservation of gametes and embryos. Despite increasing levels of regulation and the requirement to adhere to total quality management practices, catastrophic incidents such as the death of an employee or the loss of a freezer full of patient embryos or sperm continue to occur sufficiently frequently for the industry to be concerned and highlight the need to make practices considerably safer. Potential losses through litigation could be considerable if the gamete or embryo bank is found to be negligent and fails to provide the necessary resources and implement recognizable control measures, which may include suitable facilities with adequate ventilation and oxygen monitoring, competent staff, and an appropriate level of well-maintained equipment; round-the-clock emergency procedures, early warning systems to deal with a failing vessel; and contingency to mitigate losses within a failing vessel and validated procedures which are embedded into the organization which lead to a high-quality end product, for example, frozen embryo while permitting a safe system of work. Since cross-contamination incidents have occurred in other disciplines such as blood cryostorage, which have led to the transmission of viral disease, the biological safety of the end product also requires careful consideration despite the fact that no similar incident appears to have come to light in the field of reproductive medicine. Implementation of risk reduction measures may include screening for blood borne viruses and possibly bacterial infection, careful selection of appropriate packaging plastics, and consideration as to whether packaging is suitable for immersion in liquid nitrogen. If not, vapor phase storage may be considered as additional mitigation. In the light of recent events, centers should place risk management of their cryofacilities and service high on the agenda and ensure that it becomes integral to future objective setting and business planning.
Keywords: sperm; gamete; embryo; cryopreservation; risk